(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Undescended testis (cryptorchidism) is a common congenital anomaly in the male paediatric population, affecting 3-4% of full-term and up to 45% of preterm neonates. Early diagnosis and management are crucial to prevent complications such as infertility and testicular malignancy. Ultrasonography (US) is frequently used to assess undescended testis due to its non-invasive nature and availability, but its diagnostic accuracy needs comprehensive evaluation. Aims: This study evaluates the diagnostic accuracy of ultrasonography in detecting and localizing undescended testes in the paediatric population by comparing its findings with magnetic resonance imaging (MRI) and intraoperative observations. Materials and Methods: A hospital-based cross-sectional study was conducted over 18 months at Nil RatanSircar Medical College and Hospital, Kolkata, involving 150 male paediatric patients (aged 6 months–12 years) diagnosed with undescended testis. Each patient underwent ultrasonography, and the results were compared with MRI and intraoperative findings.Statistical analysis included sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy. Results: Among the 150 patients included in the study, ultrasound examination showed that the most common finding was intracanalicular location in 60 patients (40.0%), followed by superficial ring in 42 patients (28.0%), deep ring in 18 patients (12.0%), not found in 18 patients (12.0%), and intra-abdominal location in 12 patients (8.0%).MRI evaluation was performed in 40 patients, among which deep ring location was identified in 24 patients (16.0%) and intra-abdominal location in 16 patients (10.7%). MRI was not done in 110 patients (73.3%).On intraoperative findings, the most common location was intracanalicular in 60 patients (40.0%), followed by superficial ring in 42 patients (28.0%), deep ring in 27 patients (18.0%), intra-abdominal location in 16 patients (10.7%), while the structure was not found in 5 patients (3.3%). Conclusion: Ultrasonography is a valuable first-line imaging modality due to its accessibility, cost-effectiveness, and non-invasiveness. However, its limitations in detecting intra-abdominal testis necessitate supplementary imaging with MRI, particularly for non-palpable cases. A multi-modal imaging approach, integrating clinical assessment, is essential for accurate diagnosis and optimal patient management.